(Ⅰ)Sn=⇒(1-q)Sn=2-qan且q≠1
当n=1时,(1-q)S1=2-qa1⇒a1=2
当n≥2时,(1-q)Sn-(1-q)Sn-1=qan-1-qan⇒an=qan-1
∴{an}是以2为首项,公比为q的等比数列.
(Ⅱ) 当q=时,由(1)得 an=2()n-1
又 f(x)=x2+2x-,∴f′(x)=x+2
由bn+1=f′(bn)得bn+1=f′(bn)=bn+2
∴{bn}是以2为首项,公差为2的等差数列,
故bn=2n
∴cn=anbn=n()n Tn==n(n+1),
Bn=++…+=++…+=1-
An=c1+c2+…+cn=1•+2()2+…+n()n…①
∴An=1•()2+2()3+3()4+…+(n-1)()n+n()n+1…②
①-②得∴An=1•()1+()2+()3+…+()n-n()n+1
=-n()n+1=-n()n+1
∴An=1--•
∴An-Bn=1--•-1+=-=3n+1-(2n2+5n+3) |
(n+1)•3n+1 |
当n=1时,An-Bn=3n+1-(2n2+5n+3) |
(n+1)•3n+1 |
=<0
∴An<Bn
当n≥2时,
令g(x)=3x+1-(2x2+5x+3)
则g′(x)=3x+1ln3-(4x+5),g∥(x)=3x+1(ln3)2-4在[2,+∞)上为单调增函数,
∴g∥(x)=3x+1(ln3)2-4≥33(ln3)2-4>0
∴g′(x)=3x+1ln3-(4x+5)在[2,+∞)上为单调增函数,
g′(x)=3x+1ln3-(4x+5)≥33ln3-9>27-9>0
g(x)=3x+1-(2x2+5x+3)在[2,+∞)上为单调增函数,
∴当n≥2时,g(n)=3n+1-(2n2+5n+3)≥33-(2×4+10+3)>0
即当n≥2时,An-Bn=3n+1-(2n2+5n+3) |
(n+1)•3n+1 |
>0
∴当n≥2时,An>Bn
又f′(x)=x+2>0对x≥0恒成立,
∴f(x)在[0,+∞)上单调递增,
∴当n=1时f(An)<f(Bn)
当n≥2时f(An)>f(Bn).